An extended P-graph approach to process network synthesis for multi-period operations. (2nd February 2016) - Tan, Raymond R.; Aviso, Kathleen B.
Highlights: Extends P-graph approach for multi-period process network synthesis. Modification enables partial load operational lower limit for process units to be considered. A simple case illustrates the approach. Abstract: An extension of the P-graph approach for multi-period process network synthesis (PNS) is proposed in this work. A modification of a previously published approach enables partial load operational lower limit for process units to be considered via the addition of fictitious streams. A simple case study is presented to illustrate the advantages of this modified approach.